Promises and Challenges of Immunogenic Chemotherapy in Multiple Myeloma - Johnstone, Megan; Vinaixa, Delaney; Turi, Marcello; Morelli, Eugenio; Anderson, Kenneth Carl; Gulla, Annamaria (Cells, 2022)
Immunological tolerance of myeloma cells represents a critical obstacle in achieving long-term disease-free survival for multiple myeloma (MM) patients. Over the past two decades, remarkable preclinical efforts to understand MM biology have led to the clinical approval of several targeted and immunotherapeutic agents. Among them, it is now clear that chemotherapy can also make cancer cells "visible" to the immune system and thus reactivate anti-tumor immunity. This knowledge represents an important resource in the treatment paradigm of MM, whereas immune dysfunction constitutes a clear obstacle to the cure of the disease. In this review, we highlight the importance of defining the immunological effects of chemotherapy in MM with the goal of enhancing the clinical management of patients. This area of investigation will open new avenues of research to identify novel immunogenic anti-MM agents and inform the optimal integration of chemotherapy with immunotherapy.
Keywords: microenvironment; Multiple Myeloma; mnohočetný myelom; immunogenic chemotherapy; ICD; Humans; DAMPs; myeloma; lidé; Immunotherapy; imunoterapie